Spatial mismatch in diversity facets reveals contrasting protection for New Zealand's cetacean biodiversity. (March 2022) - Mouton, Théophile L.; Stephenson, Fabrice; Torres, Leigh G.; Rayment, Will; Brough, Tom; McLean, Matthew; Tonkin, Jonathan D.; Albouy, Camille; Leprieur, Fabien
Abstract: Cetaceans play key roles in the world's ecosystems and provide important economic and social benefits. New Zealand's Exclusive Economic Zone is a global biodiversity hotspot for cetaceans and benefits from a system of marine protected areas (MPAs). However, spatial patterns of cetacean biodiversity and their overlap with MPAs have never been assessed. We quantify this overlap by using a comprehensive cetacean at-sea sightings database, high-resolution environmental data layers, and information on ecological and evolutionary characteristics of each species to model spatial patterns of taxonomic, functional, and phylogenetic diversity of cetaceans. We examine areas of congruence among hotspots of richness and uniqueness components of biodiversity and measure the contribution of species to biodiversity. We find that cetacean taxonomic and phylogenetic diversity are spatially mismatched with MPAs, but this is less true for functional diversity. Hotspots of congruence among richness indices are located on the continental shelf break, whereas hotspots of uniqueness indices are located closer to shore on the continental shelf. Seven species have high contributions to biodiversity, with blue whale being the only species being evolutionarily distinct, functionally unique, specialised and globally endangered. Our results underline the potential of multicomponent biodiversity indices, their spatial congruence, and the contribution of species to biodiversity to be used as guides for a strategic placement and expansion of MPAs to protect biodiversity.